Preterm Birth Risk and Recurrence Among Multiparous Women With Congenital Uterine Anomalies [26K]. (May 2020) - Schwartz, Amanda R.; Abdalla, Azza; Wheeler, Sarahn M.; Dotters-Katz, Sarah K.
Abstract : INTRODUCTION: Women with congenital uterine anomalies (CUA) are known be at high risk for preterm birth (PTB). We sought to determine the risk of PTB among multiparous women with known CUA as stratified by previous pregnancy history. METHODS: A retrospective cohort of women with a known CUA who delivered at 2 tertiary health systems, 2013-2019. We included multiparous women who were carrying non-anomalous, singleton gestations. The primary outcome was PTB before 37 weeks; secondary outcomes included PTB before 34weeks and median delivery gestational age (GA). Women with a history of PTB were compared to those without a history of PTB using Wilcoxon rank sum, ANOVA, Fisher's exact, chi-square, and Kaplan-Meier survival curves. RESULTS: 122 multiparous women with CUA met inclusion criteria; 48 (39.3%) had a prior PTB. The most common CUA was bicornuate (43.4%) followed by septate (27.9%), unicornuate (11.5%), didelphys (10.7%), and arcuate (6.7%). PTB before 37 weeks was more common among women with a prior PTB (45.8% vs. 25.7%, P= .02), as was PTB before 34 weeks (27.1% vs. 12.2%, P= .04). In addition, women with a prior PTB delivered earlier [median 37.1 (IQR 30.9-38.4) vs. 39.0 (IQR 36.9-39.4), P= .002]. CONCLUSION: Multiparous women with CUA are at high risk for PTB. While a history of preterm birth increases risk, even women with prior term birth(s) had high rates of PTB. Overall use of prophylactic treatments such as cerclage and progestogen supplementation was low. Future studies should investigate therapeutic options for the prevention of PTB among women with CUA, irrespective of prior pregnancy history.